جرائم البناء بدون ترخيص - Khaleel, Neran; Abdullah, Kadem (Journal of Legal Sciences, 2022)
This research was tagged (building crimes without a license) to study these crimes in the Penal Code and special penal laws that dealt with this crime. And the responsibility of those in charge of Iraqi law and comparative laws. We have sought to investigate the criminal responsibility of construction workers without obtaining a license from the concerned authorities to grant building permits in the laws of the countries that regulated criminal responsibility for construction work under special penal laws such as Egypt and Algeria، and study these laws analytically compared to Iraqi law. At the end of our discussion، we assumed that the Iraqi Penal Code should include special provisions to regulate construction work، determine the criminal responsibility of those responsible for it، and hold violators of those laws accountable، as is the case in the comparative laws. In the light of this، we divided this study on two topics: We deal in the first topic: licensing and the position of some punitive legislation on the crime of construction without a license and we divided it on two requirements، the first included the concept of licensing and the position of punitive legislation on the crime of building without a license، while the second demand addressed the position of the Iraqi legislator Construction crime without a license. The second section included the elements of the crime of building without a license and the penalty prescribed for it. We divided it into three demands that dealt with the first corner of the physical crime، while the second requirement included the moral corner، while the third requirement was allocated to the penalty prescribed for the construction crime without a license. Our study ended with a conclusion that included a number of conclusions and proposals.